27%‐Efficiency Four‐Terminal Perovskite/Silicon Tandem Solar Cells by Sandwiched Gold Nanomesh. (4th November 2019) - Wang, Ziyu; Zhu, Xuejie; Zuo, Shengnan; Chen, Ming; Zhang, Cong; Wang, Chenyu; Ren, Xiaodong; Yang, Zhou; Liu, Zhike; Xu, Xixiang; Chang, Qing; Yang, Shaofei; et al.
Abstract: Multijunction/tandem solar cells have naturally attracted great attention because they are not subject to the Shockley–Queisser limit. Perovskite solar cells are ideal candidates for the top cell in multijunction/tandem devices due to the high power conversion efficiency (PCE) and relatively low voltage loss. Herein, sandwiched gold nanomesh between MoO3 layers is designed as a transparent electrode. The large surface tension of MoO3 effectively improves wettability for gold, resulting in Frank–van der Merwe growth to produce an ultrathin gold nanomesh layer, which guarantees not only excellent conductivity but also great optical transparency, which is particularly important for a multijunction/tandem solar cell. The top MoO3 layer reduces the reflection at the gold layer to further increase light transmission. As a result, the semitransparent perovskite cell shows an 18.3% efficiency, the highest reported for this type of device. When the semitransparent perovskite device is mechanically stacked with a heterojunction silicon solar cell of 23.3% PCE, it yields a combined efficiency of 27.0%, higher than those of both the sub‐cells. This breakthrough in elevating the efficiency of semitransparent and multijunction/tandem devices can help to break the Shockley–Queisser limit. Abstract : The efficiencies of semitransparent perovskite device and four‐terminal perovskite/silicon multijunction/tandem solar cells rise to 18.3% and 27.0%, respectively. This is the highest recorded efficiency for semitransparent perovskite solar cells thus far. The high efficiencies originate from good transparency and high conductivity of the nanomesh‐structured gold top electrode.